Fast fluid–structure interaction simulations using a displacement-based finite element model equipped with an explicit streamline integration prediction - Ryzhakov, P.B.; Marti, J.; Idelsohn, S.R.; Oñate, E. (Computer methods in applied mechanics and engineering, 2017)
We propose here a displacement-based updated Lagrangian fluid model developed to facilitate a monolithic coupling with a wide range of structural elements described in terms of displacements. The novelty of the model consists in the use of the explicit streamline integration for predicting the end-of-step configuration of the fluid domain. It is shown that this prediction considerably alleviates the time step size restrictions faced by the former Lagrangian models due to the possibility of an element inversion within one time step. The method is validated and compared with conventional approaches using three numerical examples. Time step size and corresponding Courant numbers leading to optimal behavior in terms of computational efficiency are identified. •Efficient displacement-based model for solving fluid–structure interaction problems.•Combination of explicit prediction of the nodal positions using integration along the streamlines with an implicit correction.•Large time steps.•Tightly coupled scheme.